1997
DOI: 10.1002/(sici)1097-4601(1997)29:6<415::aid-kin2>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the initiation step of the thermal decomposition of SiCl4

Abstract: The initiation reaction of the thermal decomposition of silicon tetrachloride (R1) was studied behind reflected shock waves at temperatures between 1550 K and 2370 K and pressures between 1 and 1.5 bar. Atomic resonance absorption spectrometry (ARAS) was applied for time-resolved measurements of H atoms at the L ␣ -line in SiCl 4 /H 2 /Ar systems. Additional experiments were performed in the SiCl 4 /Ar system following the absorption of SiCl 4 at the L ␣ -line. Rate coefficients for the reaction (R1) were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…In both studies, the high pressure limit rate constants were derived from VTST calculations as the reaction proceeds barrierless towards the resulted in final rate constants that are in close agreement with each other. These theoretical rate constants are compared in Figure 9 to the experimental values of Catoire et al 30 and Kunz and Roth 4 . It appears, from the discrepancy between the theoretical high pressure limits and the experimental values of Catoire et al, that reaction R2 must exhibit a significant pressure dependence, especially at high temperature, as suggested by the increase of the ratio k∞/kexp.…”
Section: Reaction Sicl4 + H (R1 and R5)mentioning
confidence: 96%
“…In both studies, the high pressure limit rate constants were derived from VTST calculations as the reaction proceeds barrierless towards the resulted in final rate constants that are in close agreement with each other. These theoretical rate constants are compared in Figure 9 to the experimental values of Catoire et al 30 and Kunz and Roth 4 . It appears, from the discrepancy between the theoretical high pressure limits and the experimental values of Catoire et al, that reaction R2 must exhibit a significant pressure dependence, especially at high temperature, as suggested by the increase of the ratio k∞/kexp.…”
Section: Reaction Sicl4 + H (R1 and R5)mentioning
confidence: 96%
“…The reactions involving gaseous are well known to be SiCl 4 important in the chemical vapor deposition processes used for the synthesis of SiC and Ðlms.1h3 Knowledge of the Si 3 N 4 kinetic properties of these reactions is necessary for the further development of these gas phase processes. Experimentally, Catoire et al 4…”
Section: Introductionmentioning
confidence: 99%
“…The error bars shown in the figures represent one standard deviation based on several data runs. 34 ' 35 and Powers,' 4 respectively. These papers suggested that the initial steps produce the radical SiCI 3 rather than SiCI 2 .…”
mentioning
confidence: 99%